Spirituality among Filipino adolescents - Resurreccion, Ron R. (Animo Repository, 2009)
Majority of adolescents across different cultures believe that God or a Supreme Being exists although different cultures vary in religious beliefs and practices, as well as concepts of spirituality. This qualitative study focused on how Filipino adolescents conceptualize spirituality. Data from four focused group discussions with 32 Filipino adolescents were content analyzed. Results revealed that Filipino adolescents define spirituality in terms of faith in religion, personal relationship with God, and positive character. The indicators of a spiritual person are the following: faith in God, strong sense of morality, positive personal qualities, positive sense of self, positive relationship with God' creations, altruism-based happiness and adaptive capacity to solve problems. Themes about their spiritual experiences involve self-transformation, divine inte,vention, extraordinary courage, self-insight and communion with nature. Spirituality develops through the influence of supporlive significant others, exposure to religious beliefs and practices, overcoming difficult life expenences, reconnecting with God and constant recognition of the value of spirituality. The blocks to spirituality are lack of faith in God, materialism, myopic focus on problems and decreased level of morality.